Effect of certain indigenous medicinal plants on ovarian hormone profile and reproductive performance in anestrus cattle - MEHROTRA, S; SINGH, S K; SHANKER, UMA; AGARWAL, S K (The Indian Journal of Animal Reproduction, 2005)
Considering the limitations of hormones, the plant remedies mentioned in ancient and mediaeval texts/traditional practice need to be explored scientifically to evolve suitable alternatives in correcting reproductive dysfunction. In such an attempt the effects of medicinal plants viz. Murraya koenigii (Curry leaf plant) and Urtica dioica (Bichchu grass) were observed on serum estrogen progesterone concentrations and induction of estrus and conception in anestrus cattle. Twenty crossbred anestrus cattle were divided in three groups of 7 (Mu"aya), 7 (Urtica) and 6 (control). Animals in two treatment groups were assigned with oral administration of plant powder for nine days (day 0-8) based on extrapolated doses from rats. Serum sampling was carried out on day -8, -4, 0, 4, 8, 12 and 16, and estrogen, progesterone concentrations were determined using ELISA. Onset of estrus and pregnancy establishment was recorded. Results dipicted significantly rising estrogen levels in Mu"aya treated group without altering progesterone concentrations and appreciable induction of fertility, in the same group.